Left peroneal paresis in a young female basketball player after anterior cruciate ligament reconstruction of the right knee (Indian Journal of Case Reports, 2024)
There are various reasons for the injury to the peroneal nerve but the most common cause is compression anywhere along its route, from the origin to the distal branches, usually at the knee level. At the knee level, compression on the fibular level within the course of the peroneal nerve and anatomical and pathological is the site where the peroneal nerve is usually affected. Iatrogenic injuries after surgical interventions to the knee, metabolic, or toxic causes are also common. We present the case of a young female basketball player who underwent a surgical procedure for the injured anterior cruciate ligament of the right knee and during the rehabilitation process, peroneal paresis of a left leg occurred.